TREATMENT OF CHILDREN WITH FOCAL SEGMENTAL GLOMERULAR SCLEROSIS WITH CYCLOSPORINE A - O.V. Komarova; A.N. Tsygin; L.V. Leonova; A.G. Kucherenko; O.A. Zrobok; T.V. Vashurina; M.V. Rozhkova ("Paediatrician" Publishers LLC, 2009)
The article demonstrates successful experience of treatment of focal segmental glomerular sclerosis (FSGS) with cyclosporine A in children. 25 children over the age 1,5-16 years old with FSGS were treated with cyclosporine A in medium dose 4-5 mg/kg combined with prednisolone 1-1,5 mg/kg every other day. Pulse treatment with methylprednisolone 30 mg/kg every other day, in total 3-9 injections, was administrated for the purpose of remission induction. After 5 months of treatment with cyclosporine A complete clinical and laboratory remission of steroid-resistance nephritic syndrome (SRNS) was achieved in 9 (36%) patients, partial response was registered in 6 (24%) patients, maintenance of SRNS activity was detected in 10 (40%) cases. After the year of treatment complete remission was shown in 13 (52%) children, partial response - in 5 (20%) patients, and absence of effect was registered in 7 (28%) cases. In 56% of cases, the treatment with steroids was completely stopped after achievement of SRNS remission within administration of cyclosporine A. At the present times, authors observe 14 children, whose duration of treatment with cyclosporine A is 2 years. 12 patients remain previously achieved complete or partial remission of nephritic syndrome without decrease of nitrogen excretion function of kidneys. 9 patients underwent repeated biopsy of kidneys for the exclusion of nephrotoxic effect of cyclosporine A. The results of biopsy allowed prolongation of therapy: in 6 children the previous dose maintained, and 3 children got double decreased dose. Thus, the treatment with cyclosporine A is effective in 76% of patients with FSGS. Prolongation of treatment with cyclosporine A up to 2 years and more is possible in conditions of regular diagnostic of kidneys function and absence of its nephrotoxic effect signs, according to a data from repeated biopsy. Key words: children, focal segmental glomerular sclerosis, cyclosporine, methylprednisolone. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(5):93-97)